2018
DOI: 10.24099/vet.arhiv.160720
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sex and age at slaughter on the physicochemical properties of baby-beef meat

Abstract: the aim of this study was to determine the effect of sex and age at slaughter on the physicochemical properties and quality of Simmental baby-beef. the research was conducted on 1,200 livestock, of which 600 were male and 600 female. Male cattle were slaughtered at the age of 13 to 14 months, 15 to 16 months and 17 to 18 months, while female cattle were slaughtered at the age of 12 to 13 months, 14 to 15 months and 16 to 17 months. Physicochemical properties associated with the quality of meat (ph, eC and meat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
4
7
0
1
Order By: Relevance
“…Numerically, the highest level of DFD accounted 46.15% in the age group 2 -3 years followed by age group 6 -9 years old (33.33%) and 3 -6 years (14.29%), respectively. This result was in agreement with previous research work done by [25] who reported that no significant difference among young male cattle slaughtered at different ages.…”
Section: Level Of Dark Firm Dry For Arsi Boran and Harar Beef Cattlesupporting
confidence: 94%
“…Numerically, the highest level of DFD accounted 46.15% in the age group 2 -3 years followed by age group 6 -9 years old (33.33%) and 3 -6 years (14.29%), respectively. This result was in agreement with previous research work done by [25] who reported that no significant difference among young male cattle slaughtered at different ages.…”
Section: Level Of Dark Firm Dry For Arsi Boran and Harar Beef Cattlesupporting
confidence: 94%
“…The higher L* value observed, in female meat samples compared to males are in accordance to previously reported studies (Zhang et al, 2010;Marenčić et al, 2018). Generally, higher pH values have been correlated with darker color in bull meat, due to the more rapid glycolysis appeared postmortem (Immone et al, 2000).…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 91%
“…In regard to pH values, drip loss and tenderness, the determined values are within the range reported in previous studies (Page et al, 2001;Coleman et al, 2016;Marenčić et al, 2018). Although these parameters can be affected by many factors like i.e., genotype, feeding, treatment before or after slaughter, treatment of carcass after slaughter etc., this was not observed in our study possibly either due to the high variability observed in some values (i.e., tenderness) or due to the fact that many of these parameters are corelated to each other.…”
Section: Advances In Animal and Veterinary Sciencessupporting
confidence: 84%
“…This may occur because increasing dietary linseed oil levels can affect the activity of calciumdependent enzymes, such as calpain and calpastatin. According to Marenčić, Ivanković, Kozačinski, Popović and Cvrtila (2018), factors associated with sex differences and meat tenderness include circulating hormone levels in the body, temperament and reactivity to pre-slaughter handling, as well as calpastatin activity and its association with postmortem tenderization. In this respect, Coutinho et al (2017) reported greater calpastatin activity in LM of heifers when compared to steers.…”
Section: Dm)mentioning
confidence: 99%